Geneza deklaracji londyńskiej z 3 lutego 1935 r. - Szudarek, Krystian M. (Acta Universitatis Lodziensis. Folia Historica, 2001)
The aim of this paper is to present the circumstances, which led to announcement of London Declaration and British diplomacy’s part in this regard. London communiqué exemplified another attempt of solution issue of German “equality of rights” demands in armaments and French “security” postulate. This iunctim has been included in Powers Declaration from December the 11th 1932. British diplomacy directly contributed to recognition of this principle, because the British had recognised German thesis morally and politically correct. There existed, as well, the fear of Germany’s withdrawal from Disarmament Conference and open rearmament. “Equality of rights” in diplomatic vocabulary meant rearmament. The British diplomacy tried to limit extent of German armaments through disarmament convention (MacDonald’s Plan of 15th March 1933), and after withdrawal of Germany from Geneva and breakdown of the Disarmament Conference, through arms convention (Disarmament Memo of 29th January 1934). For this reasons the British feigned ignorance with regard to German violation of the military provisions of the Peace Treaty. On 17th of April 1934, French diplomacy refused further negotiations on legalisation of German armaments, due to lack of security guarantee. However, the British diplomacy, in sequel, intended to bargain with Hitler and to reach agreement on armaments, although Defence Requirements Committee recognised Germany “as ultimate potential eneny”. But attempt to find solution in connection with negotiation on Eastern Locarno, during the summer 1934, ended with failure. At least, in November-December 1934, the British cabinet took the decision about final solution of the problem of the illegal German armaments, which was regarded as an accomplished fact. According to reports from British Embassy in Berlin, there were the threat that Hitler as first, at the beginning 1935, would propose to resume negotiation on armaments or else would present ex-Allies with a fait accompli. The British intended to take over the initiative and establish common standpoint with the French and propose to change Part V of the Treaty return for some preconditions earlier. On 22nd of December Pierre Laval, new French Foreign Secretary, accepted provisionally this proposition. The fundamental part of the formula declaration has been established through diplomatic means at the end of January 1935. Final arrangements on condition of the cancellation of the disarmament clauses ensued during visits of French ministers in London at the beginning of February 1935. Anglo-French declaration of 3th of February was the attempt to reach of a general settlement, with Hitler, and proposed negotiation: of the armaments question, Germany’s participation in Eastern, Danubian and Air Pact and Her return to the League of Nations, simultaneously. Hitler provisionally agreed to talks, but only with England and merely on Air Pact he voiced favour. Soon chancellor presented the ex-Allies with a fait accompli and British aims: limitation of armaments and Germany’s return to Geneva was not realised although individual parts of London declaration were discussed until autumn 1935.